Surface NKG2C Identifies Differentiated αβT-Cell Clones Expanded in Peripheral Blood - Kovalenko, Elena I.; Zvyagin, Ivan V.; Streltsova, Maria A.; Mikelov, Artem I.; Erokhina, Sofya A.; Telford, William G.; Sapozhnikov, Alexander M.; Lebedev, Yury B. (Frontiers in Immunology, 2021)
T cells that express CD56 in peripheral blood of healthy humans represent a heterogeneous and poorly studied subset. In this work, we analyzed this subset for NKG2C expression. In both CD56+ and CD56– subsets most of the NKG2C+ T cells had a phenotype of highly differentiated CD8+ TEMRA cells. The CD56+NKG2C+ T cells also expressed a number of NK cell receptors, such as NKG2D, CD16, KIR2DL2/DL3, and maturation marker CD57 more often than the CD56–NKG2C+CD3+ cells. TCR β-chain repertoire of the CD3+CD56+NKG2C+ cell fraction was limited by the prevalence of one or several clonotypes which can be found within the most abundant clonotypes in total or CD8+ T cell fraction TCR β repertoire. Thus, NKG2C expression in highly differentiated CD56+ T cells was associated with the most expanded αβ T cell clones . NKG2C+ T cells produced almost no IFN-γ in response to stimulation with HCMV pp65-derived peptides. This may be partially due to the high content of CD45RA+CD57+ cells in the fraction. CD3+NKG2C+ cells showed signs of activation, and the frequency of this T-cell subset in HCMV-positive individuals was positively correlated with the frequency of NKG2C+ NK cells that may imply a coordinated in a certain extent development of the NKG2C+ T and NK cell subsets under HCMV infection.